Serpentine soils affect heavy metal tolerance but not genetic diversity in a common Mediterranean ant. (August 2017) - Frizzi, Filippo; Masoni, Alberto; Çelikkol, Mine; Palchetti, Enrico; Ciofi, Claudio; Chelazzi, Guido; Santini, Giacomo
Abstract: Natural habitats with serpentine soils are rich in heavy metal ions, which may significantly affect ecological communities. Exposure to metal pollutants results, for instance, in a reduction of population genetic diversity and a diffused higher tolerance towards heavy metals. In this study, we investigated whether chronic exposure to metals in serpentine soils affect accumulation patterns, tolerance towards metal pollutants, and genetic diversity in ants. In particular, we studied colonies of the common Mediterranean ant, Crematogaster scutellaris, along a contamination gradient consisting of two differently contaminated forests and a reference soil with no geogenic contamination. We first evaluated the metal content in both soil and ants' body. Then, we tested for tolerance towards metal pollutants by evaluating the mortality of ants fed with nickel (Ni) solutions of increasing concentrations. Finally, differences in genetic diversity among ants from different areas were assessed using eight microsatellite loci. Interestingly, a higher tolerance to nickel solutions was found in ants sampled in sites with intermediate levels of heavy metals. This may occur, because ants inhabiting strongly contaminated areas tend to accumulate higher amounts of contaminants. Additional ingestion of toxicants beyond the saturation threshold would lead to death. There was no difference in the genetic diversity among ant colonies sampled in different sites. This was probably the result of queen mediated gene flow during nuptial flights across uncontaminated and contaminated areas of limited geographical extent. Highlights: Ants in serpentine soils are affected by the presence of heavy metals. Here we test the effect of exposure to nickel on the ant Crematogaster scutellaris . Chronic exposure to intermediate metal levels increases ants' tolerance to nickel. Microsatellites analysis reveals no detectable effect on genetic diversity.